Key Audit Matters: Influences and Relevance for Stakeholders A review of the academic literature: Array - Porumbacean, Teodora; Tiron-Tudor, Adriana (The Journal of Accounting and Management, 2022)
Following the financial crisis, standard-setters proposed multiple methods to improve the auditor’s report quality in order to also increase the financial stability. Thus, the audit report was expanded to include an additional section for the disclosure of the Key Audit Matters. The paper aims to provide a review of 24 academic research papers by assessing three streams of information in respect to the perception of the stakeholders regarding KAMs communication. The paper’s findings reveal that there are still debated opinions in terms of KAMs utility. The first set of results showed that due to this expansion of the auditor’s report an increase in the quality of the financial reporting was noted and the user’s perceived reliability was improved, resulting also in a decrease of the expectation gap. The second stream of research papers analysed revealed that the audit fee increased and so did the auditor’s and implicitly the litigation risk and despite the purpose of ISA 701, the transparency level did not increase. Finally, the last set of papers addressed neutral opinions, showing that there is still no sufficient market reaction to assess the utility of KAMs.